IMPLEMENTASI PENILAIAN AUTENTIK KURIKULUM 2013 DALAM PEMBENTUKAN KARAKTER SISWA DI SDIT INAYAH UJUNGBATU KABUPATEN ROKAN HULU PROVINSI RIAU - Mardiani Mardiani; Abdul Putra Ginda Hasibuan (JURNAL PENDIDIKAN ROKANIA, 2020)
This article was written to see the implementation of the 2013 curriculum authentic assessment in the formation of student character at SDIT Inayah Ujungbatu Rokan Hulu, Riau Province. Sourced from the results of research with qualitatve descriptive research. Data collection methods through observation, interviews, and documentation. The results obtained are (1) The understanding of SDIT Inayah Ujungbatu teachers on the implementation of authentic 2013 assessmnets shows an average of 79% which is in the good category. (2) Description of character education at SDIT Inayah Ujungbatu 100% shows that is well implemented, character education at SDIT Inayah Ujungbatu is not only done at the time of assessment, but starts from student coming to school in the morning (3) Supporting factors for the 2013 authentic assessment implementation is the guidance of supervisors and principals, training, KKG, book review, peer tutors.